2021
DOI: 10.23863/kalem.2021.182
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Dönemde Çocuğu Olan Babaların Baba Çocuk İlişkileri ve Babalık Rolü Algıları Arasındaki İlişkinin İncelenmesi: Gaziantep İli Örneği

Abstract: Araştırmanın amacı, okul öncesi dönemde çocuğu olan babaların babalık rolü algıları ile baba çocuk ilişkisi arasındaki ilişkinin incelenmesidir. İlişkisel tarama modelinde desenlenmiş olan araştırmanın örneklemi 3-6 yaş grubunda çocuğu olan ve araştırmaya gönüllü olarak katılan 1015 babadan oluşturulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
0
0
1
Order By: Relevance
“…It can be stated that the generalized effect size value calculated according to the random effect model represents a moderate effect according to Cohen et al's (2007) classification. It was observed that the effect size value obtained regarding the relationship between emotion regulation difficulties and depression was similar to the research results (Akcan & Taşören, 2020;Güzel et al, 2021;Wu et al, 2019). As a result of the literature review, no study findings were found for the purpose of the study.…”
Section: Discussionsupporting
confidence: 86%
“…It can be stated that the generalized effect size value calculated according to the random effect model represents a moderate effect according to Cohen et al's (2007) classification. It was observed that the effect size value obtained regarding the relationship between emotion regulation difficulties and depression was similar to the research results (Akcan & Taşören, 2020;Güzel et al, 2021;Wu et al, 2019). As a result of the literature review, no study findings were found for the purpose of the study.…”
Section: Discussionsupporting
confidence: 86%
“…Günümüzde geleneksel aile yapısı yerini modern çekirdek aileye bırakmaktadır. Aile içerisindeki iş bölümünün de geleneksellikten uzaklaşarak yerini daha eşitlikçi bir paylaşıma bıraktığı görülmektedir (Aktürk, 2015;Bayer, 2013;Chin, Hall ve Daiches, 2011;Crespi ve Ruspini, 2015;Czymoniewicz-Klippel, 2019;Dempsey ve Hewitt, 2012;Dick, 2011;Eggebeen ve Knoester, 2001;Güzel, Tüfekçi, 2021;Johansson, 2011;Lamb, 2000;Zeybekoğlu, 2013).…”
unclassified